KARAKTERISTIK KEPAILITAN BADAN HUKUM KOPERASI (Lex Journal: Kajian Hukum & Keadilan, 2019)
This study aims to determine the construction of bankruptcy law associated with the characteristics of cooperative legal entities. The approach used is a statutory approach, a conceptual approach, and a case approach. The source of legal material consists of primary legal material and secondary legal material.The results of the study show that  cooperative legal entities are activities carried out by a group of people or groups that prioritize family-based activities, cooperation, mutual cooperation based on equality, rights and obligations to achieve common goals, namely the welfare of all members cooperatives This is what gives birth to two dimensions of cooperatives, namely the social dimension and the economic dimension namely achieving prosperity through cooperation and mutual cooperation that works based on the ideal foundation, structural foundation and operational foundation. In the event of bankruptcy, the filing of cooperative bankruptcy should be carried out by the Ministry of Cooperatives after the efforts of guidance and supervision by the Ministry of Cooperatives.